Factors Associated with Compliance to Iron Supplementation Tablet Consumption Among Adolescent Girls in Coastal Area of West Lombok - As Shiddiq, Muhammad Hilmy; Lestarini, Ima Arum; Restuningdyah, Novia Andansari Putri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Anemia remains a major health problem among adolescent girls in Indonesia, with significant implications for reproductive health and productivity. Since 2014, the government has implemented an iron supplementation program through schools, yet compliance remains low. This study aimed to analyze the relationship between family support, teacher support, peer support, and socioeconomic status with compliance to iron tablet consumption among adolescent girls at SMAN 1 Lembar. This was an analytical observational study with a cross-sectional design. A total of 84 students were selected using purposive sampling. Data were collected through a validated and reliable online questionnaire and analyzed using the Chi-Square test. The results showed significant associations between teacher support (p<0.05) and peer support (p<0.05) with compliance to iron tablet consumption, while family support and socioeconomic status showed no significant associations (p>0.05). In conclusion, compliance with iron tablet consumption among adolescent girls is more strongly influenced by teacher and peer support than by family or socioeconomic factors. Strengthening school involvement and peer influence may serve as effective strategies to improve adherence and enhance anemia prevention programs.